1988
DOI: 10.1007/bf01941703
|View full text |Cite
|
Sign up to set email alerts
|

Casein, a prohormone with an immunomodulating role for the newborn?

Abstract: Maternal colostrum and milk, the earliest food of the newborn, should not only be considered as supplying nutrients, but also as agents providing protection against aggressions from the new environment. Indeed by enzymatic digestion of the main milk proteins, the caseins, biologically active peptides are released; they may be implicated in the stimulation of the newborn's immune system. From this point of view a 'strategic active zone' has been characterized in beta-casein. A possible role of casein as a 'proh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 49 publications
0
47
0
3
Order By: Relevance
“…This sequence has been defined as a strategic zone (Migliore-Samour & Jolle´s, 1988;Meisel, 1998). The sequence is protected from proteolysis because of its high hydrophobicity and the presence of proline residues.…”
Section: Other Functionalitiesmentioning
confidence: 99%
“…This sequence has been defined as a strategic zone (Migliore-Samour & Jolle´s, 1988;Meisel, 1998). The sequence is protected from proteolysis because of its high hydrophobicity and the presence of proline residues.…”
Section: Other Functionalitiesmentioning
confidence: 99%
“…It was demonstrated that peptides from α s1 -casein (residues 194-199 and 23-34) and β-casein (residues 63-68 and 191-193) stimulate phagocytosis by murine peritoneal macrophages and consequently exert a protective effect against Klebsiella pneumoniae infection in mice aft er intravenous treatment (25,(27)(28)(29)(30)(31). The peptide α s1 -casein (residues 23-34) was demonstrated to be produced in Parmigiano Reggiano during ripening (19).…”
Section: Immunomodulatory Peptidesmentioning
confidence: 99%
“…The most abundant peptides are derived from β-CN, reflecting its high susceptibility to plasmin-mediated proteolysis as well as the high content of this casein subunit in HM (14,16). Focusing on bioactive peptides in undigested HM, as shown in Table 1 (14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), two caseinophosphopeptide homologues, a possible opioid peptide or propeptide, and an antibacterial peptide were identified.…”
Section: In Vitro Digestion Of Human Milk Proteinmentioning
confidence: 99%